2019
DOI: 10.2147/cmar.s192361
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-526b-3p serves as a prognostic factor and regulates the proliferation, invasion, and migration of glioma through targeting WEE1</p>

Abstract: Background: MicroRNAs play important roles in cancer progression including glioma. In this study, we aimed to explore the expression pattern, prognostic potential, and functional role of miR-526b-3p in human glioma. Materials and methods: The expression of miR-526b-3p in glioma tissues and the adjacent non-tumor tissues was determined by quantitative RT-PCR. The chi-square test was performed to evaluate the statistical associations between miR-526b-3p level and patient charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…29 Recently, several studies demonstrated that WEE1 were implicated in tumor growth and metastasis in laryngeal carcinoma, glioma, non-small cell lung cancer, bladder cancer and hepatocellular carcinoma. [30][31][32][33][34] In this study, we observed that miR-194-5p could directly target WEE1 3ʹUTR and regulating its expression, which was consistent with Li's report of miR-194 targeting WEE1 in laryngeal squamous cell carcinoma. 35 Additionally, HEIH knockdown significantly reduced WEE1 expression via miR-194-5p.…”
Section: Dovepresssupporting
confidence: 91%
“…29 Recently, several studies demonstrated that WEE1 were implicated in tumor growth and metastasis in laryngeal carcinoma, glioma, non-small cell lung cancer, bladder cancer and hepatocellular carcinoma. [30][31][32][33][34] In this study, we observed that miR-194-5p could directly target WEE1 3ʹUTR and regulating its expression, which was consistent with Li's report of miR-194 targeting WEE1 in laryngeal squamous cell carcinoma. 35 Additionally, HEIH knockdown significantly reduced WEE1 expression via miR-194-5p.…”
Section: Dovepresssupporting
confidence: 91%
“…Those three genes included in the model were WEE1, SEMA4G, CRTAC1. It has been reported that WEE1 is closely related to the growth, invasion and migration of glioma (Wu et al, 2019). Currently, there is no study revealing the role of SEMA4G and CRTAC1 in gliomas.…”
Section: Resultsmentioning
confidence: 99%
“…WEE1 prolongs the G2 phase via controlling the activity of CDK1, thus allowing more time for DNA repair . WEE1 is up‐regulated in diverse tumors to exert carcinogenic effects, such as in laryngeal squamous cell carcinoma, neuroblastoma, and glioma, implying that WEE1 may be a promising target for cancer treatment . Furthermore, it has been demonstrated that WEE1 expression is modulated by multiple miRNAs.…”
Section: Discussionmentioning
confidence: 52%
“…40,41 WEE1 is up-regulated in diverse tumors to exert carcinogenic effects, such as in laryngeal squamous cell carcinoma, neuroblastoma, and glioma, implying that WEE1 may be a promising target for cancer treatment. [42][43][44] Furthermore, it has been demonstrated that WEE1 expression is modulated by multiple miRNAs. For instance, miR-503 enhances the radiosensitivity of laryngeal cancer cells via targeting WEE1.…”
Section: Discussionmentioning
confidence: 99%